2005
DOI: 10.1002/pssc.200461607
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stimulated current spectroscopy and photoluminescence of carbon‐doped semi‐insulating GaN grown by ammonia‐based molecular beam epitaxy

Abstract: Semi-insulating GaN samples, grown by ammonia-based molecular beam epitaxy and doped with carbon, were investigated by thermally stimulated current spectroscopy and photoluminescence at 4.2 K. In addition to a dominant trap at 0.90 eV, thought to be related to the N interstitial, a trap at 0.50 eV, presumably related to C Ga , was observed in the samples with high carbon concentrations. For all of the carbon-doped samples, strong photoluminescence (PL) bands were observed in the yellow (YL), blue (BL), and nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…In a subsequent TSC study of carbondoped semi-insulating GaN, grown by ammonia-based molecular beam epitaxy ͑MBE͒, trap B x ͑0.50 eV͒ was found to dominate in the high-carbon sample ͓͑C͔ =8ϫ 10 18 cm −3 ͒ and was tentatively assigned to C Ga . 11 The impact of carbon on trap states in n-type GaN grown by MOCVD was also studied by both DLTS and DLOS. 12 From a comparison of the DLOS measurements on low-pressure grown codoped GaN:C:Si and atmospheric-pressure grown UID GaN, two deep levels, at 1.35 and 3.28 eV below the conduction band, were observed to have a direct relation with excess carbon incorporation.…”
Section: Figmentioning
confidence: 99%
“…In a subsequent TSC study of carbondoped semi-insulating GaN, grown by ammonia-based molecular beam epitaxy ͑MBE͒, trap B x ͑0.50 eV͒ was found to dominate in the high-carbon sample ͓͑C͔ =8ϫ 10 18 cm −3 ͒ and was tentatively assigned to C Ga . 11 The impact of carbon on trap states in n-type GaN grown by MOCVD was also studied by both DLTS and DLOS. 12 From a comparison of the DLOS measurements on low-pressure grown codoped GaN:C:Si and atmospheric-pressure grown UID GaN, two deep levels, at 1.35 and 3.28 eV below the conduction band, were observed to have a direct relation with excess carbon incorporation.…”
Section: Figmentioning
confidence: 99%
“…It is important to note that the photo response ͑or photocurrent per 1 V͒ in both types of samples is many orders of magnitude higher than that in carbon-doped semi-insulating GaN materials. In a previous study, 9 the carbon-doped GaN layers showed saturated photocurrent of less than 0.2 pA under 100 V bias and 360 nm light excitation. This indicates that the UID semi-insulating/ resistive GaN materials have significantly longer effective carrier lifetime than the carbon-doped GaN materials.…”
Section: High Resistivity Measurement Resultsmentioning
confidence: 78%
“…The luminescence properties of the carbon-doped GaN have been reported and discussed in a previous paper. 9 Because of the high carbon ͑in the order of 10 19 cm −3 ͒ and associated oxygen ͑in the order of 10 18 cm −3 ͒ concentrations, radiative recombination of excitons is suppressed by prevailing nonradiative recombination centers that were introduced by the carbon-doping process. The nonradiative centers may involve carbon and oxygen impurities and their complexes formed with native defects.…”
Section: High-resistivity Gan Versus Conducting Ganmentioning
confidence: 99%
See 2 more Smart Citations